The graphic and historical illustrator | an original miscellany of... - Internet Archive Book... (Wikimedia Commons, 1834)
Notice visuelle issue de Wikimedia Commons pour la demo du fonds documentaire.
Licence No known copyright restrictions via Wikimedia Commons
Keywords: histoire; iconographie; gravure; photographie; wikimedia commons